2011
DOI: 10.1051/fruits/2011032
|View full text |Cite
|
Sign up to set email alerts
|

Variabilité morphologique du baobab (Adansonia digitataL.) au Mali

Abstract: Morphological variability of the baobab tree (Adansonia digitata L.) in Mali.Abstract -Introduction. Baobab (Adansonia digitata L.) is a typical agricultural landscape tree in semi-arid areas of Africa. It is a tree used daily by the local population. The diversity of its services and products suggests an assessment of its morphological variability to achieve a better understanding of its potential. This article seeks to identify morphological descriptors of baobab in relation to the agro-ecological diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
(8 reference statements)
2
9
0
1
Order By: Relevance
“…These parameters were highlighted by Nafan [17] in Vitellaria paradoxa (Shea) as the most variable. The same was true for Detarium microcarpum [18].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…These parameters were highlighted by Nafan [17] in Vitellaria paradoxa (Shea) as the most variable. The same was true for Detarium microcarpum [18].…”
Section: Discussionsupporting
confidence: 54%
“…These authors have shown that the size and shape of the fruits make it possible to identify different phenotypes of these trees. One other author obtained similar results in Andansonia digitata [18]. Moreover, since fruiting is an important step in the development cycle, it remains influenced by various factors that would be responsible for variability.…”
Section: Discussionmentioning
confidence: 54%
“…[6] showed that the most discriminative variables of baobab type of capsules in Benin are the length and number of seeds, the size and weight of pulps-seeds, the total weight of capsules and the ratio length/width of capsules. [4] in Burkina Faso indicated that the same Morphometric parameters underlined by [6] characterize with high variability baobab. As afr as Sclerocarya birrea is concerned, discriminative parameters are the diameter of fruits, the number of seeds, the seeds weight, the bole height and the number of primary branches [8].…”
Section: Morphometric Characteristics Of P Africanamentioning
confidence: 99%
“…Many studies had already concerned the variability of species showing great interest to the local populations. Among studies concerning morphological variability of species, one can underline those of [4] on Adansonia digitata in Mali, [5] on Argania spinosa in the South-West Morocco, [6] on Adansonia digitata in Benin, [7] and [8] on Sclerocarya birrea in Benin and in Burkina Faso, and [9] on Milicia excelsa. Some studies related to morphologic variability of Prosopis species were carried out by selected authors such as [10] on Prosopis juliflora and Prosopis pallida, of [11] and of [12].…”
Section: Introductionmentioning
confidence: 99%
“…En Afrique de l'Ouest, plusieurs études ont révélé la richesse numérique des espèces composant les zones de forêts et savanes ainsi que la diversité des utilisations qui en sont faites [1][2][3][4][5][6][7][8][9][10][11][12][13]. Parmi les espèces utilitaires, les lianes, qu'elles soient ligneuses ou herbacées, occupent une place importante.…”
Section: Introductionunclassified